AN ANALYSIS OF NAMING IN JOURNALISM: sexual and gender dissidence in Folha de S. Paulo - de Santana, Eder Luis Cordeiro (Brazilian journalism research, 2020)
This article is part of a study which establishes naming as a foundation of journalism. Two objectives are worked on: (1) identify how LGBTQI+1 people were named in Folha de S. Paulo in the twentieth and twenty-first centuries; (2) present a three-stage methodological proposal: content analysis (Bardin, 2016), observation of framing and sources, an statement analysis based on the Foucaultian perspective of discourse. The corpus is a collection of content published in the month of June from five different decades: 1969, 1979, 1989, 1999 and 2009. The period from which the material was selected used the Stonewall riots2 as a historical milestone. Este artigo faz parte de uma pesquisa voltada a pensar a nomeação como fundamento do jornalismo. São trabalhados dois objetivos: (1) identificar como pessoas LGBTQI+ foram nomeadas na Folha de S. Paulo em diferentes contextos históricos entre os séculos XX e XXI; (2) apresentar proposta metodológica dividida em três etapas: análise de conteúdo (Bardin, 2016), observação do framing e das fontes e, por fim, uma análise enunciativa baseada em perspectiva foucaultiana do discurso. Foram coletados como corpus conteúdos publicados no mês de junho em cinco diferentes décadas: 1969, 1979, 1989, 1999 e 2009. O período determinado para seleção do material levou em consideração a Revolta de Stonewall como marco histórico. Este artículo es parte de una investigación centrada en nomimación como la base del periodismo. Se elaboran dos objetivos: (1) identificar cómo las personas LGBTQI + fueron nombradas en Folha de S. Paulo en diferentes contextos históricos entre los siglos XX y XXI; (2) presentan una propuesta metodológica dividida en tres etapas: análisis de contenido (Bardin, 2016), observación de framing y fuentes y, finalmente, un análisis enunciativo basado en la perspectiva foucaultiana del discurso. Se recopiló como contenido del corpus publicado en el mes de junio en cinco décadas diferentes: 1969, 1979, 1989, 1999 y 2009. El período determinado para la selección del material tuvo en cuenta la rebelión de Stonewall como un hito histórico.